Characteristics of Beef Cattle Breeders in the Artificial Insemination Technology Service Program in Pohuwato Regency - Yusri T. Datau; Mahludin Baruwadi; Muhammad Sayuti; La Ode Sahara (International journal of technology and education research, 2025)
Abstract This study aims to analyze the characteristics of livestock breeders in the Artificial Insemination Technology Service Program in Pohuwato Regency. This study used a survey method with primary data collection through interviews and questionnaires with livestock respondents. Secondary data were obtained from relevant agencies. Data analysis used descriptive statistical analysis. The results showed that 56.7% of livestock farmers receiving Artificial Insemination Program services in Pohuwato Regency were in the productive age range of 41-60 years. Most, or 64.45% of livestock farmers only had an elementary school education or equivalent and had more than 10 years of livestock farming experience. Farmers owned between 1-3 beef cattle (46.67%). The scale of livestock ownership was relatively small and only a side business so it was included in the category of smallholder livestock. Farmers who had received and adopted artificial insemination technology for more than 9 years were 51.11%. The majority of farmers were considered to have had sufficient adoption experience so that supporting the success of artificial insemination services depended not only on semen quality and inseminator skills, but also on the farmer's experience in reproductive management.